2019
DOI: 10.1534/genetics.119.302056
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Effective Ploidy Drive Genome-Wide Endosperm Expression Polarization and Seed Failure in Wild Tomato Hybrids

Abstract: Parental imbalances in the endosperm leading to impaired development and eventual hybrid seed failure are common causes of postzygotic isolation in flowering plants. Endosperm sensitivity to parental dosage is reflected by canonical phenotypes of “parental excess” in reciprocal interploid crosses. Moreover, parental-excess traits are also evident in many homoploid interspecific crosses, potentially reflecting among-lineage variation in “effective ploidy” driven by endosperm properties. However, the genetic bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 66 publications
3
49
0
Order By: Relevance
“…We interpret the pattern of S. peruvianum dominance as consistent with the rationale of the weak inbreeder/strong outbreeder (WISO) hypothesis (Brandvain and Haig 2005), with the S. peruvianum genome ‘overpowering’ that of S. chilense , which putatively evolved under lower levels of parental conflict. These inferences are in accordance with our prior and current evidence for higher effective ploidy of S. peruvianum compared to S. chilense (Roth et al 2019), and how it plausibly underpins seeds’ developmental and phenotypic differences between these two wild tomato lineages: smaller hybrid seed size and transcriptomic signals (Florez-Rueda, Paris, et al 2016; Roth, Florez-Rueda, Griesser, et al 2018; Roth et al 2019), such as a higher proportion of DE genes, DE sRNAs, and larger shifts toward maternal allelic expression in PC (compared to CP) hybrid endosperm.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We interpret the pattern of S. peruvianum dominance as consistent with the rationale of the weak inbreeder/strong outbreeder (WISO) hypothesis (Brandvain and Haig 2005), with the S. peruvianum genome ‘overpowering’ that of S. chilense , which putatively evolved under lower levels of parental conflict. These inferences are in accordance with our prior and current evidence for higher effective ploidy of S. peruvianum compared to S. chilense (Roth et al 2019), and how it plausibly underpins seeds’ developmental and phenotypic differences between these two wild tomato lineages: smaller hybrid seed size and transcriptomic signals (Florez-Rueda, Paris, et al 2016; Roth, Florez-Rueda, Griesser, et al 2018; Roth et al 2019), such as a higher proportion of DE genes, DE sRNAs, and larger shifts toward maternal allelic expression in PC (compared to CP) hybrid endosperm.…”
Section: Discussionsupporting
confidence: 93%
“…MADS-domain TFs have been shown to play key regulatory roles in plant reproduction, in particular in regulating female gametophyte, embryo, and endosperm development (reviewed in Masiero et al 2011). Likewise, AGAMOUS-LIKE ( AGL ) genes were jointly overexpressed in ‘paternal-excess-like’ crosses involving S. chilense , S. peruvianum , and S. arcanum (Roth et al 2019). These TFs are part of the GO protein dimerization activity (GO:0046983) and include 11 AGL genes, 13 2FE-2S FERREDOXIN-LIKE genes, three PHERES genes, APETALLA3 and SEPALATA3 , among others (supplementary tables S3, S6, Supplementary Material online).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, when we increased N. tabacum ploidy, type II seed abortion was prevented, leading to suppression of another postzygotic reproductive barrier-ovary abscission. This is likely due to the direct relationship between type II seed abortion and ovary abscis- (Coughlan et al, 2020;Lafon-Placette et al, 2018;Roth et al, 2019;). In the present study, we can infer that the relative effective ploidies between N. suaveolens accessions are PI 555565 (8x) ≈ PI 555561 (16x)> PI 555561 (8x) ≈ PI 555568 (8x)> PI 555568 (4x).…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal endosperm development in interspecific crosses between species with the same ploidy level can be bypassed by changing the ploidy of one parental species (Bushell et al, 2003;Johnston and Hanneman, 1982;Lafon-Placette et al, 2017;Tonosaki et al, 2018). Moreover, genome-wide studies on endosperm gene expression have revealed that genomic imprinting is extensively perturbed in failing hybrid endosperm in Solanum, Capsella and several other species (Lafon-Placette et al, 2018;Roth et al, 2019;Tonosaki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%